ANATOMY AND SYSTEMATICS OF THE PTEROSAUR CARNIADACTYLUS GEN. N. ROSENFELDI (DALLA VECCHIA, 1995) (Rivista italiana di Paleontologia e Stratigrafia, 2009)
The holotype specimen of the non-pterodactyloid pterosaur Eudimorphodon rosenfeldi from the Late Triassic (Norian) of NE Italy is described in detail and compared to the other specimens referred in literature to the genus Eudimorphodon. It is considered conspecific with the specimen MPUM 6009 from the Norian of NW Italy, previously attributed to Eudimorphodon ranzii. A new genus, Carniadactylus, is proposed for the two specimens based on the apomorphic shape of the "coronoid" process, coracoid and pteroid, wing phalanx proportions and the several anatomical differences with E. ranzii and "Eudimorphodon" cromptonellus. No definitive evidence of a juvenile stage occurs in the two specimens. A phylogenetic analysis using parsimony shows that Carniadactylus is nested inside the Campylognathoididae and is the sister-group of Caviramus schesaplanensis + "Raeticodactylus" filisurensis. The systematics of specimens referred in the literature to Eudimorphodon is reviewed.